Enhancing English Education Program Students’ Skill In Writing Essay Through Clustering Technique - Rina Puji Utami (Dharma Pendidikan, 2018)
This study aims to determine the enhancing of students’ writing achievement using clustering technique .The usage of this technique is expected that the students’ achievement in writing skill can increase. The clustering technique used in writing learning of this study uses argumentative essays using various topics in accordance with the focusing understanding and making the essays of writing courses for the fourth semester students, at English Education Program of STKIP PGRI Nganjuk in the academic year of 2017/2018. The total number of students is 18 students . The increasing in students’ achievement can be known by the analysis the result score in this study by using the classroom action research that is intended to find out that the clustering technique can help the students improve and develop their ability in writing skill. The grand of mean score test in preliminary study was 70,5 and cycle I was 75, while the grand mean score in cycle 2 was 87 which showed this present study could be categorized successful because it had exceeded the minimum criteria of writing III.